Perancangan dan Pembangunan Aplikasi Electronic Menu Restoran - Nurpandi, Finsa; Liki, Diki M Rosid (Teknik Informatika Universitas Suryakancana Cianjur, 2021)
Electronic Menu or abbreviated as eMenu is an application that designed to improve the performance of service processes in a business sector, especially restaurants. eMenu aims to change thefood ordering service process that was originally traditional using paper, into web-based digital media. Not only handling food ordering services, eMenu also handles almost all business processes in a restaurant such as menu management, managing information on orders received by waiters and chef, payment transactions, to sales reports. To handle payment transaction, eMenu using third party application payment gateway, called Duitku. eMenu is built using Single-Page Application concept that use AJAX calls which allows time efficiency in displaying the required data. By using the Single-Page Application, the browser does not reload the entire requested page but only part of data is displayed dynamically. The Single-Page Application uses Vue.js as Front-end stack, and Laravel to manage Back-end. eMenu application is responsive design, so that user can access via smartphone or desktop computer with properly.